Obmowa, obmawianie, oczernianie w polskich gwarach - Wysoczański, Włodzimierz (LingVaria, 2025)
BACKBITE, BACKBITING, SLANDER IN POLISH DIALECTS The subject of the study includes the acts of backbite, backbiting and slander occurring in Polish dialects. On the basis of the material in the form of vocabulary and phrasematics, the following topics are discussed in detail: the act of backbite and the phenomenon of backbiting, approximating the scope of backbite (links to specific speech acts), the circumstances and places conducive to backbiting, the ones being backbitten, the ones backbiting; the speech activity of slander, defining the scope of this act (co-dependence with other speech acts); together backbiting and slander, bringing out the aspects of correlation between these acts (co-contextuality in relation to gossiping, spoiling opinions) and highlighting the issues of creating names associated with these speech acts. The consideration of verbal acts of backbite, backbiting and slander presents a peculiar segment in the circulation of messages perpetuated in the dialects. It also reveals the specific characteristics of the considered speech acts, as well as the co-dependence of backbiting and slander.